An acquired Gerbode defect from the left ventricle to the coronary sinus following mitral valve replacement. Issue 6 (24th May 2017) - Collis, Richard; Afoke, Jonathan; McGregor, Christopher GA
Abstract: We report the management of an acquired Gerbode defect, from the left ventricle to the coronary sinus, following mechanical mitral valve replacement. Following a failed percutaneous closure, surgical patch closure of the defect was performed.